Dynamic changes in physiological and biochemical properties of flue-cured tobacco of different leaf ages during flue-curing and their effects on yield and quality - Chen, Yanjie; Ren, Ke; He, Xian; Gong, Jiangshiqi; Hu, Xiaodong; Su, Jiaen; Jin, Yan; Zhao, Zhengxiong; Zhu, Yanmei; Zou, Congming (BMC plant biology, 2019)
The leaf age for harvesting flue-cured tobacco leaves is closely related to the quality of tobacco leaves, so an appropriate leaf age for harvesting is important for improving yield and quality of flue-cured tobacco, however, at present, there are few studies on effects of leaf age on physiological and biochemical changes during flue-curing and there is no clear standard of proper leaf ages for harvesting in production. In the Yunnan tobacco-growing area, an experiment was carried from 2016 to 2017 and different leaf ages were set. The results demonstrate that leaf age has a significant on tissue cell gap, leaf age and flue-curing stages exert significant effects on upper epidermis, palisade and spongy tissue, and leaf thickness of tobacco leaves. The thicknesses of upper and lower epidermis as well as palisade and spongy tissues at different ages show an approximately W-shaped change trend during flue-curing. With the advance of flue-curing stages, contents of starch, chlorophyll, carotenoid, and water in tobacco leaves at different leaf ages decrease, while polyphenol and malondialdehyde (MDA) contents increase. The older the leaf, the faster the chlorophyll, carotenoid, and water contents reduce, while the faster the polyphenol and MDA content rise during flue-curing. The flue-cured tobacco leaves at 116 DAT (days after transplanting) show the highest contents of total nitrogen and nicotine, followed by 123 DAT and those at 130 DAT are the lowest; however, the contents of total sugar and reducing sugar demonstrate a contrary tendency, and the starch content at 116 DAT is much lower than those in the other two treatments. The proportion of superior tobacco, average price, yield, and output value of upper tobacco leaves at different leaf ages are the highest at 123 DAT. The highest sensory evaluation score is found at 123 DAT, while that at 130 DAT is significantly lower in comparison with the other two treatments. Tobacco leaves harvested at 123 DAT are mature and exhibit a low degree of membrane lipid peroxidation, moderate chemical compositions, and high economic value. 123 DAT improves availability of tobacco leaves.